Implementasi Prinsip Al-Maslahah dalam Pelayanan Publik Berbasis Digital di Nganjuk: Perspektif Fiqh Siyasah - Ahmad Suhaimi; Nurul Syalafiyah (Bahasa Indonesia, 2025)
The background of digital transformation in public services is driven by societal demands for quick, easy, and transparent services. This shift must be evaluated not only from a technical efficiency standpoint but also through the lens of ethical and legal values, specifically the Islamic principle of Al-Maslahah. This study aims to analyze the implementation of digital-based public services in Nganjuk Regency through the perspective of the Al-Maslahah principle (which seeks to protect religion, life, intellect, progeny, and wealth) and the theory of Fiqh Siyasah (Islamic political policy). The research employs a qualitative approach with a case study method. Data was collected through in-depth interviews with Civil Servants (ASN) and service users, observation, and documentation studies of the Nganjuk Regency Government's digital service websites and applications. The findings indicate that service digitalization in Nganjuk aligns with the principle of Al-Maslahah, particularly in realizing maslahah mursalah (unrestricted public interest) to achieve public benefit (jalb al-mashalih), such as time and cost efficiency. However, challenges such as the digital divide and data security vulnerabilities were acknowledged, potentially leading to mafsadah (harm). In conclusion, this digitalization policy can substantially be categorized as Siyasah Syar'iyyah (Sharia-oriented policy), which is valid under Islamic law as long as it is oriented towards achieving public benefit and minimizing harm, as taught in Fiqh Siyasah.